Downward Nominal Wage Rigidity in Europe - Steinar Holden; Fredrik Wulfsberg (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper explores the existence of downward nominal wage rigidity (DNWR) in the industry sectors of 14 European countries, over the period 19731999, using a data set of hourly nominal wages at industry level. Based on a novel nonparametric statistical method, which allows for country and year-specific variation in both the median and the dispersion of industry wage changes, we reject the hypothesis of no DNWR. The fraction of wage cuts prevented due to DNWR has fallen over time, from 70 percent in the 1970s to 20 percent in the 1990s, but the number of industries affected by DNWR has increased. Wage cuts are less likely in countries and years with high inflation, low unemployment, high union density and strict employment protection legislation.
Keywords: 330; downward nominal wage rigidity; European countries; employment protection legislation